Effect of unilateral training and bilateral training on physical performance: A meta-analysis - Zhang, Wenfeng; Chen, Xing; Xu, Kun; Xie, Hezhi; Li, Duanying; Ding, Shicong; Sun, Jian (Frontiers in Physiology, 2023)
Background: In Unilateral (UNI) exercises are more effective than bilateral (BI) exercises in improving athletic performance is debatable. Objectives: this meta-analysis investigated the effects of UNI and BI exercises on different effect indicators of jump ability, sprint ability, maximal force, change of direction ability, and balance ability. Data Sources: PubMed, Google Scholar, Web of science, CNKI, Proquest, Wan Fang Data. Study Eligibility Criteria: To be eligible for inclusion in the meta-analysis, the study had to be: 1) athletes; 2) UNI training and BI training; 3) the intervention period had to be more than 6 weeks and the intervention frequency had to be more than 2 times/week; 4) the outcome indicators were jumping ability, sprinting ability, maximum strength, and change of direction and balance. Study Appraisal and Synthesis Method: We used the random-effects model for meta-analyses. Effect sizes (standardized mean difference), calculated from measures of horizontally oriented performance, were represented by the standardized mean difference and presented alongside 95% confidence intervals (CI). Results: A total of 28 papers met the inclusion criteria, and Meta-analysis showed that UNI training was more effective than BI training in improving jumping ability (ES = 0.61.0.23 to 0.09; Z = 3.12, p = 0.002 < 0.01), sprinting ability (ES = −0.02, −0.03 to −0.01; Z = 2.73, p = 0.006 < 0.01), maximum strength (ES = 8.95,2.30 to 15.61; Z = 2.64, p = 0.008 > 0.05), change of direction ability (ES = −0.03, −0.06 to 0.00; Z = 1.90, p = 0.06 > 0.01) and balance ability (ES = 1.41,-0.62 to 3.44; Z = 1.36, p = 0.17 > 0.01). The results of the analysis of moderating variables showed that intervention period, intervention frequency and intervention types all had different indicators of effect on exercise performance. Conclusion: UNI training has a more significant effect on jumping and strength quality for unilateral power patterns, and BI training has a more significant effect on jumping and strength quality for bilateral power patterns.